Middle hepatic vein incorporation in live donor liver graft transplantation; implication and safety - Abdi, Mahmoud Ali; Kareem, Tayeb Sabir; Hassoun, Assad Abidon (Kurdistan Journal of Applied Research, 2021)
Background: In this study, we have used the middle hepatic vein with the right lobe, and we studied the venous outflow dynamics immediately after transplant retrospectively meanwhile we studied the impact of the graft function on donor functionality and overall donor safety. Method: Between October 2017 to October 2020, we performed 40 adult to adult live donor liver transplants at Zheen International Hospital (Erbil, Kurdistan Region). Postoperative Doppler ultrasound was performed for recipients and donors immediately after surgery and then daily until discharge. Results: The donor age (28.5 ± 6.9) year, male/ female 19/ 21, intensive care unit stay (1.2 ± 0.43), floor stay (5.2 ± 1.4) days, their portal vein velocity (43.5 ± 18.4 ml/sec), hepatic artery resistive index (0.6 ± 0.09) and triphasic/ continuous venous outflow 30/10, their postoperative day one and at the discharge total serum bilirubin were (2.8 ± 1.8) and (2 ± 1.4), their postoperative day one and at the discharge international normalization ratio were (1.7 ± 0.5) and (1.2 ± 0.2) respectively. The recipient age (48.5 ± 11.3), male/female 27/13, intensive care unit stay (4.75 ± 3.9), floor stay (7.7 ± 3.7) days, portal vein velocity (63.96 ± 24.65 ml/sec), hepatic artery peak systolic velocity (74.76 ± 32.85) hepatic artery resistive index (0.7 ± 0.15), and triphasic/continuous venous outflow 27/13. Conclusions: Middle hepatic vein incorporation in live donor liver graft is safe with a favorable outcome for recipient and donor, doppler US is one the important tool for evaluation and follow up of donor and recipient for detection of vascular complications and assessment of venous outflow and graft function. In addition, early discharge of the donor is a reasonable option.